Nursing care for type 2 diabetes mellitus patients with the application of diabetic foot gymnastics: A quasi-experimental study - Aulia, Siti; Prasert, Somchai (Indonesian Journal of Health Services, 2024)
Background: Type 2 diabetes mellitus is a chronic metabolic disease that frequently leads to complications such as peripheral neuropathy, impaired circulation, and decreased mobility in the lower extremities. These complications often reduce patients’ functional capacity and increase the risk of diabetic foot problems. Non-pharmacological interventions that support circulation and nerve function are therefore important components of comprehensive diabetes care. Diabetic foot gymnastics has been recommended as a simple and practical exercise to improve lower limb circulation and prevent neuropathic complications. However, evidence regarding the effectiveness of nursing-led diabetic foot exercise programs in clinical care settings remains limited. Objective: This study aimed to evaluate the effectiveness of nursing care for patients with type 2 diabetes mellitus through the application of diabetic foot gymnastics using a quasi-experimental approach. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted among 60 patients with type 2 diabetes mellitus. Participants were divided into an intervention group (n=30) and a control group (n=30). The intervention group received structured diabetic foot gymnastics training as part of nursing care, while the control group received routine diabetes care without the exercise program. The intervention was implemented for four weeks with regular supervised sessions. Outcome variables included neuropathic pain, peripheral circulation measured by capillary refill time, and lower extremity mobility. Data were analyzed using descriptive and inferential statistical tests to compare pre- and post-intervention outcomes. Results: The intervention group demonstrated a significant reduction in neuropathic pain scores, improved peripheral circulation, and increased mobility after the exercise program. The average pain score decreased from 6.4 to 3.2, capillary refill time improved from 3.1 seconds to 2.1 seconds, and mobility scores increased from 52.8 to 68.5. In contrast, the control group showed only minimal changes in these indicators. Conclusion: Diabetic foot gymnastics integrated into nursing care effectively improves neuropathic symptoms, circulation, and functional mobility in patients with type 2 diabetes mellitus. The intervention provides a practical strategy for nurses to support prevention and management of diabetic neuropathy in clinical practice.